Matthew - Quarles, Charles L. (Exegetical Guide to the Greek New Testament, 2017)
I. Introduction (1:1-4:16) -- II. Galilean Ministry (4:17-16:20) -- III. Journey to Jerusalem (16:21-20:34) -- IV. Jerusalem ministry (21:1-28:20).